1992
DOI: 10.1103/physrevlett.68.1156
|View full text |Cite
|
Sign up to set email alerts
|

Role of phonon dimensionality on electron-phonon scattering rates

Abstract: Electron-heating measurements were carried out to measure the electron-phonon scattering rates in CuCr thin films. We examined free-standing and supported films whose thickness and width span lengths comparable to the mean thermal-phonon wavelength. The measured scattering rate was proportional to T 2 from 0.5 to 10 K, independent of sample configuration. We observe that the quantization of the phonon spectrum required by sample dimensions has no effect on the temperature dependence of the electron-phonon scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
65
0

Year Published

1993
1993
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(69 citation statements)
references
References 16 publications
4
65
0
Order By: Relevance
“…Using (19) and (21) and changing from summations over k and q to integrals, for the symmetric part we have…”
Section: Contribution Of the S Modesmentioning
confidence: 99%
See 1 more Smart Citation
“…Using (19) and (21) and changing from summations over k and q to integrals, for the symmetric part we have…”
Section: Contribution Of the S Modesmentioning
confidence: 99%
“…has a temperature dependence proportional to T x e − T x ph , where x < 5 [17][18][19] . On the other hand, a theoretical investigation of the surface effects for a thin metallic film deposited on a half-space (semi-infinite) dielectric showed that the value of x is actually larger than 5 20 .…”
Section: Introductionmentioning
confidence: 99%
“…In a dirty limit with ql < 1, theories predict that n ranges from 4 to 6 depending on type and level of disorder 17,18 . Deviations from n = 5 are experimentally observed in normal metals and alloys [19][20][21][22] . But this hypothesis is still not fully verified as some experiments show that even for samples in the dirty limit, the energy flow rate from electrons to phonons follows the T 5 dependence 23,24 .…”
mentioning
confidence: 99%
“…But this hypothesis is still not fully verified as some experiments show that even for samples in the dirty limit, the energy flow rate from electrons to phonons follows the T 5 dependence 23,24 . The effect of phonon dimensionality and substrate properties on e-p coupling have also been discussed 19,[25][26][27] . Experiments show that n falls below 4.5 for phonons in two dimensions 25 .…”
mentioning
confidence: 99%
“…The electron-phonon interaction is accordingly enhanced. This behavior was also observed in experiments [131][132][133].…”
Section: Hot-electron Effect In Bulk Resistorssupporting
confidence: 67%